AN INTEGRATIVE MODEL OF SUSTAINABLE TOURISM VILLAGES: SYNERGIZING EDUCATION, GREEN ECONOMY, AND TECHNOLOGICAL INNOVATION WITHIN THE SDGS FRAMEWORK - Setiawan, Muhammad Ozi; Suryantari, Yulita; Anom, Alfatri (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: This study aims to formulate a sustainable tourism village development model based on the Sustainable Development Goals (SDGs) through the integration of education, green economy, and innovation and technology. This research employs a qualitative method with a literature review approach, in which data were collected through an in-depth analysis of national and international academic literature indexed in Scopus, Web of Science, and Sinta with a publication year limitation from 2016 to 2025. This approach was chosen as it is considered appropriate for identifying conceptual patterns, comparing findings, and systematically formulating an integrative model of sustainable tourism village development. The findings reveal that quality education serves as a key factor in enhancing the human resource capacity of local communities, the implementation of a green economy contributes to more inclusive and equitable economic growth, while innovation and technology accelerate the transformation toward adaptive and sustainable tourism development. The main finding of this study shows that the synergy between education, green economy, and technological innovation acts as the primary driver in creating a sustainable tourism village model that is adaptive to global dynamics and aligned with the SDG principles. Nglanggeran Tourism Village is positioned as a model of sustainable rural tourism that reflects the successful integration of these three dimensions. This study concludes that the synergy of education, green economy, and technological innovation is the key to developing sustainable, adaptive, and inclusive tourism villages that remain relevant to global challenges. The implications of this study strengthen the literature on SDG-based sustainable tourism development models and provide practical guidance for governments and tourism village managers, particularly in designing inclusive, innovative, and environmentally friendly development strategies. Keywords: Sustainable Tourism; Inclusive Rural Tourism Model; Nglanggeran. Abstrak: Penelitian ini bertujuan merumuskan model pengembangan desa wisata berkelanjutan berbasis Sustainable Development Goals (SDGs) melalui integrasi pendidikan, ekonomi hijau, serta inovasi dan teknologi. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kepustakaan, di mana data dikumpulkan melalui telaah mendalam terhadap literatur akademik nasional dan internasional yang terindeks Scopus, Web of Science, dan Sinta dengan batasan tahun publikasi 2016–2025. Pendekatan ini dipilih karena dinilai tepat untuk mengidentifikasi pola konseptual, membandingkan temuan, serta merumuskan model integratif desa wisata berkelanjutan secara sistematis. Hasil kajian menunjukkan bahwa pendidikan berkualitas menjadi faktor kunci dalam peningkatan kapasitas sumber daya manusia masyarakat lokal, penerapan ekonomi hijau berkontribusi terhadap pertumbuhan ekonomi yang inklusif dan berkeadilan, sementara penguatan inovasi dan teknologi berperan mempercepat transformasi menuju pembangunan pariwisata yang berkelanjutan dan adaptif. Temuan utama dari penelitian ini menunjukkan bahwa sinergi antara pendidikan, ekonomi hijau, dan inovasi teknologi menjadi penggerak utama dalam menciptakan model desa wisata berkelanjutan yang adaptif terhadap dinamika global dan selaras dengan prinsip SDGs. Desa Wisata Nglanggeran diposisikan sebagai model desa wisata berkelanjutan yang mencerminkan keberhasilan integrasi ketiga dimensi tersebut. Penelitian ini menunjukkan bahwa sinergi pendidikan, ekonomi hijau, dan inovasi teknologi merupakan kunci dalam menciptakan desa wisata berkelanjutan yang adaptif, inklusif, dan sesuai dengan prinsip SDGs, sekaligus relevan dalam menghadapi tantangan global. Implikasi penelitian ini memperkuat literatur mengenai model pengembangan pariwisata berkelanjutan berbasis SDGs serta memberikan panduan praktis bagi pemerintah dan pengelola desa wisata, khususnya dalam merancang strategi pembangunan yang inklusif, inovatif, dan ramah lingkungan. Kata Kunci: Pariwisata Berkelanjutan; Model Desa Wisata Inklusif; Nglanggeran.